To expand the expression \((x - 6)(-3x^2 - 5x - 2)\), we can use the distributive property (also known as the FOIL method for binomials). Each term in the first polynomial will be multiplied by each term in the second polynomial.
-
Multiply \(x\) by each term in \(-3x^2 - 5x - 2\): \[ x \cdot (-3x^2) = -3x^3 \] \[ x \cdot (-5x) = -5x^2 \] \[ x \cdot (-2) = -2x \]
-
Now, multiply \(-6\) by each term in \(-3x^2 - 5x - 2\): \[ -6 \cdot (-3x^2) = 18x^2 \] \[ -6 \cdot (-5x) = 30x \] \[ -6 \cdot (-2) = 12 \]
-
Now, combine all the terms obtained from the multiplications: \[ -3x^3 + (-5x^2) + (-2x) + 18x^2 + 30x + 12 \]
-
Combine like terms: \[ -3x^3 + (-5x^2 + 18x^2) + (-2x + 30x) + 12 \] \[ -3x^3 + 13x^2 + 28x + 12 \]
So, the expanded expression in standard form is: \[ \boxed{-3x^3 + 13x^2 + 28x + 12} \]